PENGARUH KONSENTRASI POC AIR KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT(Capsicum frutescens) - Komang Dean Ananda; Ni Putu Eka Pratiwi; Ramdhoani; I Nyoman Aditya Wirananta Kusuma (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Production of rawit pepper in Bali has decreased from 2020 to 2022. By 2020, production of chili in Bali will be around 43,380 tonnes, while by 2022 production will significantly decrease to 34,948 tonnes, so the purpose of this research is to find out the influence of different coconut water POC concentrations on the polybag system on the growth and yield of ravit Pepper plants to get the right POC water concentration of coconut pepper in rawit plants. The scheme used in the study is a group random scheme (RAK), with 6 treatments POC coconut water i.e. P0=Control, P1=100 ml/liter of water, P2=200 ml/litre of air, P3=300 ml/Liter of Water, P4=400ml/Litre of Water, P5=500 ml /Liter. The result of the administration of POC Coconut Water P5 500 ml/1 litre of water gives the best results such as plant height 48,25 cm, number of leaves 33.75 strands, amount of flowers 7.5 flowers, volume of fruit 3.5 pieces, fresh fruit 3.88 g and wet weight of crop 38.43 g. The effect of the POC water administration is the lowest occurred on POC water supply P0 (control) such as crop height 27 cm, the number of strands 20.75 leaves, the amount of flower 2.25, fruit 1.75 amount of fruit, the weight of fresh fruit 2.50 g and moist weight of the crop 15.63 g. Conclusion Research results of the influence of POC concentrations of coconut water on growth parameters and the yield of pepper crops show a very real influence on all parameters